Co-operative Investment Policy as a Tool to Accelerate the Entrepreneurship and Improve the Poverty Condition in Bangladesh - Kamrul Alam, Raju Mohammad; Hossain, Md. Nazmul; Al Humssi, Ahmad (European Journal of Sustainable Development, 2019)
Bangladesh is one of the poorest countries in the world with low GDP/capita and minimum purchasing power. A third of the total population (24.3%) lives below the national poverty line ($2/day) while a half of them do live in extreme poverty level ($1.25). It’s now a national issue as high rate of poverty is the cause of permanent economic downturn and socio-economic depression in Bangladesh. Many policies have been applied by government and NGOs since its independent in 1971 to alleviate the poverty but no policy has brought a remarkable outcome. The main purpose of the study is to examine the causes for high rate of poverty in Bangladesh and insufficiency of the government agencies that are working to alleviate the poverty and propose innovative approaches to growth of entrepreneurship to bring sustainable economic growth and improve the poverty condition. The study is based on structural and semi-structural questionnaires and face to face interview. A total of 60 structural and same numbers of semi-structural questionnaires were given to 100 recipients of various age, sex, education, profession and economic levels regarding the factors to get feedback. In this research, a cooperative investment policy and a government action plan have been drawn up based on coordination between the various agencies, which allow the impoverished section of the population to save and invest collectively in order to involve them in entrepreneurship to lift themselves out of the poverty cycle and bring sustainable development. The aim of the research involving the impoverished population to entrepreneurship through co-operative investment policy and promoted government mechanisms to improve the poverty condition in Bangladesh. Search tasks: *To examine the major reasons for the high rate of poverty in Bangladesh. *To explore the impacts of entrepreneurship to accelerate the economic growth and improve the poverty condition in Bangladesh. *To discover the most effective ways to involve the impoverished population to entrepreneurship. *To develop a co-operative investment policy and an integrated government strategy covering all financial, administrative, supervisory and regulatory aspects that will regulate the state's action to accelerate the entrepreneurship and achieve economic growth. Subject of the research cooperative investment policy and improved government mechanism for poverty reduction in Bangladesh through entrepreneurship growth. Object of the research the rate of poverty, entrepreneurship. Keywords: Impoverished Population, Co-operative Investment Policy, Entrepreneurship, Government Performance, Sustainable Development.